2018
DOI: 10.1016/j.neuron.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Filopodia Conduct Target Selection in Cortical Neurons Using Differences in Signal Kinetics of a Single Kinase

Abstract: Dendritic filopodia select synaptic partner axons by interviewing the cell surface of potential targets, but how filopodia decipher the complex pattern of adhesive and repulsive molecular cues to find appropriate contacts is unknown. Here, we demonstrate in cortical neurons that a single cue is sufficient for dendritic filopodia to reject or select specific axonal contacts for elaboration as synaptic sites. Super-resolution and live-cell imaging reveals that EphB2 is located in the tips of filopodia and at nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…Photoactivatable versions of Trks have been reported and their stimulation with light for 48 hr induces neurite outgrowth in DIV1-3 dissociated neurons and de novo formation of axonal filopodia within 30 min (Chang et al, 2014), but the effects on spine formation and synaptic transmission in mature neurons have not been measured yet. Short-term photoactivation of another tyrosine kinase, EphB2, leads within seconds to the retraction of nonstabilized dendritic filopodia (Mao et al, 2018) and within minutes to the induction of new filopodia by activating actin polymerization (Locke et al, 2017). Those effects are likely to obey different downstream signaling pathways than the ones we report here and which highly depend on Nlg1 and the associated PSD scaffold.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Photoactivatable versions of Trks have been reported and their stimulation with light for 48 hr induces neurite outgrowth in DIV1-3 dissociated neurons and de novo formation of axonal filopodia within 30 min (Chang et al, 2014), but the effects on spine formation and synaptic transmission in mature neurons have not been measured yet. Short-term photoactivation of another tyrosine kinase, EphB2, leads within seconds to the retraction of nonstabilized dendritic filopodia (Mao et al, 2018) and within minutes to the induction of new filopodia by activating actin polymerization (Locke et al, 2017). Those effects are likely to obey different downstream signaling pathways than the ones we report here and which highly depend on Nlg1 and the associated PSD scaffold.…”
Section: Discussionmentioning
confidence: 68%
“…Hence, there is a pressing need for alternative paradigms allowing for an acute control of Nlg signaling pathways (Jeong et al, 2017) without affecting its expression level. Optogenetics is ideally suited for such purpose and was successfully implemented not only to regulate neuronal excitability and homeostasis, but also for fine tuning protein-protein interactions and signaling pathways in neurons with light (Berlin et al, 2016;Berlin and Isacoff, 2017;Chang et al, 2014;Goold and Nicoll, 2010;Grubb and Burrone, 2010;Mao et al, 2018;Schwechter et al, 2013;Sinnen et al, 2017;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A role for E-cadherin has been demonstrated for clustering of mouse beta cells (Dahl et al, 1996), but a filopodial enrichment of E-cadherin in relation to contact formation has not yet been confirmed. Eph/Ephrin signaling mediates bi-directional signaling during development (Caviglia and Ober, 2018), and localization of components to dendritic filopodial tips influences filopodial behavior during sampling and eventual selection of synaptic targets by neurons (Mao et al, 2018). Expression of Ephs and Ephrins in pancreatic beta cells has been shown to be important for regulating glucose secretion (Jain and Lammert, 2009), however, roles for these proteins in islet formation remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that lessons about myelin targeting may be learned from dendritic and axonal interactions during synaptogenesis, a resemblance we had noted before ( Almeida and Lyons, 2014 ). For instance, a recent study showed that dendritic filopodia of cortical neurons select or reject axonal contacts for synaptogenesis based simply on the kinetics of EphB2 signaling, whereby transient activation leads to filopodia retraction while sustained activation predicts stabilization and synaptogenesis ( Mao et al, 2018 ). It will be interesting to determine if Eph signaling kinetics in OPC processes also predict target selection or rejection ( Figure 1E ).…”
Section: How Are Targeting Signals Transduced Into Myelinating Behavimentioning
confidence: 99%